Interleukin-2 and interleukin-2 receptor expression in human corticotrophic adenoma and murine pituitary cell cultures. - Arzt, E (1992)
The production of IL-1 and IL-6 by pituitary cells has recently been demonstrated. In this study we investigated the expression of IL-2 and its receptor (IL-2R) by pituitary cells of different species. In Northern blots, a single hybridizing band of 1 kb, identical to that in normal stimulated lymphocytes, was obtained with specific IL-2 probes. In the mouse AT-20 pituitary tumor cell line, IL-2 mRNA expression was detected after stimulation with corticotropin-releasing hormone or phorbol myristate acetate. In human corticotrophic adenoma cells, basal IL-2 mRNA expression as well as IL-2 secretion were further stimulated by phorbol myristate acetate. Both adenoma and AtT-20 cells showed detectable amounts of IL-2R mRNA and by immunofluorescence, IL-2R membrane expression. In addition, dual immunofluorescence studies in rat anterior pituitary cells demonstrated colocalization of IL-2R with ACTH-positive cells and other cell types expressing the receptor. In addition to the action of lymphocyte-produced IL-2, this cytokine may have a paracrine or autocrine regulatory role within the pituitary. It remains to be established whether IL-2 production occurs in the normal pituitary or is intrinsic to the process of tumor development of these cells. IL-2 may be involved in the growth control of pituitary cells.